2019
DOI: 10.1016/j.scriptamat.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Single-step sintering of zirconia ceramics using hydroxide precursors and Spark Plasma Sintering below 400 °C

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible. This is an author's version published in: https://oatao.univ-toulouse.fr/23846Official URL : https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Among other low temperature sintering techniques, Cool-SPS was used to densify thermodynamically fragile materials, including reactive sintering of hydrated precursors at temperatures below 400°C [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among other low temperature sintering techniques, Cool-SPS was used to densify thermodynamically fragile materials, including reactive sintering of hydrated precursors at temperatures below 400°C [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Spark plasma sintering (SPS), as a relatively new powder metallurgy (P/M) technique, is well-suited for the preparation of IN718 alloy due to its assurance of high fabrication efficiency, relative density, and compressive strength of the SPS IN718 material [15]. Compared with other P/M techniques, SPS is assisted by a highly-pulsed DC, which provides the heat directly inside the sample by the Joule effect [16]. With the simultaneous application of uniaxial pressure, the samples can be fabricated rapidly by SPS [17].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The first materials produced by CSP were mainly salts and soluble compounds, 3,16 although several activities have been then carried out on ferroelectrics, [16][17][18] piezoelectrics, 19 magnetic ceramics, 20 semiconductors, [21][22][23] transparent ceramics, 24 bioceramics, 14 and ionic conductors. [25][26][27] More recent works regard water-assisted cold processing of silicate ceramics including cold sintering of quartz, 28 soda-lime silicate glass, 15 and quartz-PTFE composite 29 or cold joining of silica 30 and cold isotactic pressing of glass monoliths. 31 Although CSP is inspired by phenomena taking place in nature (like the formation of sedimentary rocks 32 ), no research activities regarding the application of CSP on nonsynthetic industrial minerals have been reported to the best of the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The first materials produced by CSP were mainly salts and soluble compounds, 3,16 although several activities have been then carried out on ferroelectrics, 16–18 piezoelectrics, 19 magnetic ceramics, 20 semiconductors, 21–23 transparent ceramics, 24 bioceramics, 14 and ionic conductors 25–27 . More recent works regard water‐assisted cold processing of silicate ceramics including cold sintering of quartz, 28 soda‐lime silicate glass, 15 and quartz‐PTFE composite 29 or cold joining of silica 30 and cold isotactic pressing of glass monoliths 31 …”
Section: Introductionmentioning
confidence: 99%